2020
DOI: 10.7150/thno.41648
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell programs in cancer initiation, progression, and therapy resistance

Abstract: Over the past few decades, substantial evidence has convincingly revealed the existence of cancer stem cells (CSCs) as a minor subpopulation in cancers, contributing to an aberrantly high degree of cellular heterogeneity within the tumor. CSCs are functionally defined by their abilities of self-renewal and differentiation, often in response to cues from their microenvironment. Biological phenotypes of CSCs are regulated by the integrated transcriptional, post-transcriptional, metabolic, and epigenetic regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
217
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 289 publications
(219 citation statements)
references
References 345 publications
(346 reference statements)
1
217
0
1
Order By: Relevance
“…Growing evidence suggests that tumor metastasis is not only determined by epigenetic or genetic networks in cancer cells but is also influenced by the tumor microenvironments [ 4 , 5 ]. Cancer-associated fibroblasts (CAFs), the main component of tumor stroma in tumor microenvironments, can build-up the cross-talk with cancer cells to facilitate tumor growth, metastasis, immunosuppression, and chemoresistance as well as the creation of a niche for maintaining cancer stemness [ 6 9 ]. In human lung cancer, the tumor microenvironment harbors abundant CAFs that secrete IGF-II, a signaling molecule that binds to IGF1R on lung CSCs to activate Akt/Nanog cascades, which play crucial roles in maintaining lung cancer stemness [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence suggests that tumor metastasis is not only determined by epigenetic or genetic networks in cancer cells but is also influenced by the tumor microenvironments [ 4 , 5 ]. Cancer-associated fibroblasts (CAFs), the main component of tumor stroma in tumor microenvironments, can build-up the cross-talk with cancer cells to facilitate tumor growth, metastasis, immunosuppression, and chemoresistance as well as the creation of a niche for maintaining cancer stemness [ 6 9 ]. In human lung cancer, the tumor microenvironment harbors abundant CAFs that secrete IGF-II, a signaling molecule that binds to IGF1R on lung CSCs to activate Akt/Nanog cascades, which play crucial roles in maintaining lung cancer stemness [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic characteristics of CSCs include self-renewal and multipotent properties, as well as proliferative potential, which give certain cellular subpopulations the ability to initiate, develop, and progress cancer (Huang et al, 2020). Dormant CSCs may be activated by a series of gene mutation accumulations and undergo a significant number of DNA sequence alterations (Sengupta and Cancelas, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A lot of convincing evidences have revealed that the existence of cancer stem cells (CSCs) is responsible for HCC metastasis, recurrence and heterogeneity [16]. Here, we identified the knockdown of NRP1 suppresses the population of CSCs representative surface markers (CD133 + /EpCAM + /CD13 + ), inhibits the migration of HCC cells and the recurrence and prognosis of HCC patients.…”
Section: Discussionmentioning
confidence: 92%